2010
DOI: 10.2478/s11535-010-0056-7
|View full text |Cite
|
Sign up to set email alerts
|

Diet overlap between small ruminants and the European hare in a Mediterranean shrubland

Abstract: Seasonal diets of goats, sheep and European hares (Lepus europaeus) were examined using microhistological analysis of feces collected when these herbivores grazed together in a typical Mediterranean shrubland. Approximately half of the total diet content of goats was shrubs (mainly kermes oak, Quercus coccifera), while that of hares was grasses (mostly brush grass, Chrysopogon gryllus). Sheep had a more balanced diet consisting mainly of grasses, forbs, and shrubs. Dietary overlap between goats and sheep was h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
9
1
2
Order By: Relevance
“…Although we examined a smaller number of hare stomachs in comparison with other studies in more northern European farmlands (Frylestam 1986;Hansen 1996;Reichlin et al 2006;Katona et al 2010), we found a higher number of plant species eaten by hares. In comparison with studies carried out in the Mediterranean, we found more plant taxa than Karmiris and Nastis (2010) in their small shrubland study area (300 ha). On the contrary, Sfougaris et al (2006) and Kontsiotis et al (2011) found a remarkably higher number of identified plant taxa when examining the autumn and winter diet of 318 and 217 hares, respectively.…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Although we examined a smaller number of hare stomachs in comparison with other studies in more northern European farmlands (Frylestam 1986;Hansen 1996;Reichlin et al 2006;Katona et al 2010), we found a higher number of plant species eaten by hares. In comparison with studies carried out in the Mediterranean, we found more plant taxa than Karmiris and Nastis (2010) in their small shrubland study area (300 ha). On the contrary, Sfougaris et al (2006) and Kontsiotis et al (2011) found a remarkably higher number of identified plant taxa when examining the autumn and winter diet of 318 and 217 hares, respectively.…”
Section: Discussioncontrasting
confidence: 76%
“…in the wet season. Higher consumption of grasses in winter has been found in continental Europe (e.g., Reichlin et al 2006), whereas in yearround studies in Mediterranean mountainous and shrubland areas, the consumption of grasses was also found to increase slightly in winter (Paupério and Alves 2008;Karmiris and Nastis 2010).…”
Section: Discussionmentioning
confidence: 80%
“…El Aich et al [19] also confirmed that goats consume a wider variety of plant species during the summer and fall, which enlarges their diet breadth. The green season is characterized by high feed offers and the appearance of some high palatable species [74], which are preferred by goats. Therefore, goats included in their diet only the high palatable species, which could explain the low diet diversity recorded during this season.…”
Section: Diet Diversity and Overlapmentioning
confidence: 99%
“…European hare eats Vicia cracca subsp. stenophylla, Dianthus zonatus and Sedum caespitosum (Reichlin et al, 2006;Karmiris and Nastis, 2010;Karmiris and Tsiouvaras, 2013;Freschi et al, 2015). European hare eats the leaves and the other parts of Vicia cracca subsp.…”
Section: Arum Dioscoridis Var Spectabile Quercus Libani Andmentioning
confidence: 99%
“…Despite the fact that European hare lives in relatively dense forest regions, located between 1500 m and 1670 m, spoilt juniper areas with high diversity of plant species and communities, forestation areas, and agricultural areas are most preferred habitat types (Oğurlu, 1997 generally prefers open habitats covered with vegetation (Peschel et al, 2011;Süel et al, 2013). This animal uses Juniperus oxycedrus for hiding and shelter purposes (Karmiris and Nastis, 2010).…”
Section: Arum Dioscoridis Var Spectabile Quercus Libani Andmentioning
confidence: 99%